Managing hyperlipidaemia in patients with COVID-19 and during its pandemic: An expert panel position statement from HEART UK. (November 2020) - Iqbal, Zohaib; Ho, Jan Hoong; Adam, Safwaan; France, Michael; Syed, Akheel; Neely, Dermot; Rees, Alan; Khatib, Rani; Cegla, Jaimini; Byrne, Christopher; Qureshi, Nadeem; Capps, Nigel; et al.
Abstract: The emergence of the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which causes Coronavirus Disease 2019 (COVID-19) has resulted in a pandemic. SARS-CoV-2 is highly contagious and its severity highly variable. The fatality rate is unpredictable but is amplified by several factors including advancing age, atherosclerotic cardiovascular disease, diabetes mellitus, hypertension and obesity. A large proportion of patients with these conditions are treated with lipid lowering medication and questions regarding the safety of continuing lipid-lowering medication in patients infected with COVID-19 have arisen. Some have suggested they may exacerbate their condition. It is important to consider known interactions with lipid-lowering agents and with specific therapies for COVID-19. This statement aims to collate current evidence surrounding the safety of lipid-lowering medications in patients who have COVID-19. We offer a consensus view based on current knowledge and we rated the strength and level of evidence for these recommendations. Pubmed, Google scholar and Web of Science were searched extensively for articles using search terms: SARS-CoV-2, COVID-19, coronavirus, Lipids, Statin, Fibrates, Ezetimibe, PCSK9 monoclonal antibodies, nicotinic acid, bile acid sequestrants, nutraceuticals, red yeast rice, Omega-3-Fatty acids, Lomitapide, hypercholesterolaemia, dyslipidaemia and Volanesorsen. There is no evidence currently that lipid lowering therapy is unsafe in patients with COVID-19 infection. Lipid-lowering therapy should not be interrupted because of the pandemic or in patients at increased risk of COVID-19 infection. In patients with confirmed COVID-19, care should be taken to avoid drug interactions, between lipid-lowering medications and drugs that may be used to treat COVID-19, especially in patients with abnormalities in liver function tests. Graphical abstract: Image 1 Highlights: Patients with ASCVD and obesity are at increased risk of severe illness and mortality if infected with COVID-19. There is no convincing evidence to suggest harm from lipid lowering therapy if patients develop SARS-CoV-2. Patients treated for hyperlipidaemia should not interrupt their treatment because of COVID-19 pandemic. Continue lipid lowering therapy in patients with confirmed diagnosis of COVID-19 unless possible risks outweigh benefits. In patient treated for COVID-19, drug interactions with lipid lowering therapies should be investigated and assessed.